Temporal Variation and Concentration Weighted Trajectory Analysis of Lead in PM10 Aerosols at a Site in Central Delhi, India. (8th December 2014) - Chandra, Subhash; Kulshrestha, Monika J.; Singh, Ruchi
Abstract : Ambient levels of lead (Pb) in PM10 were studied at a site in Central Delhi for the period of one year during day and night. The annual mean concentration of lead has been observed as 625 and 1051 ng/m 3 during day and night time, respectively. The seasonal averaged concentrations of Pb have followed the order winter > postmonsoon > summer > monsoon. Highest levels of lead have been observed in winter with 31% samples exceeding the CPCB-NAAQS value as 1000 ng/m 3 . Lead levels during winter have been found to be 5.7 times higher than in monsoon, which might be attributed to prevailing meteorological conditions and more biomass burning. The low levels of Pb during summer might be attributed to its higher dispersion in the atmosphere. A sharp rise of Pb during postmonsoon might be linked to the local nonpoint sources, more biomass burning, and shifting of boundary layer. However, the higher concentrations of lead were observed during night time in all the seasons of the year as compared to those of the day time. To identify the potential source regions of Pb, Concentration Weighted Trajectories (CWT) have been plotted which showed higher influence of local sources during winter and postmonsoon while showing distant sources during summer.